L'assemblage par collage d'œuvres d'art contemporain en PMMA - Aurélie Compère (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Various objects made out of PMMA (Plexiglas®…) are submitted to conservators when broken. The possibility of restoration by collage, essential to preserve its longevity, can be critical. This material, sensitive to many chemical mixed products, could be permanently damaged. A study allowed to compare various adhesive in order to establish the right method, used notably on Martha Boto’s Structure Optique A.